Invasive conifers reduce seed set of a native Andean cedar through heterospecific pollination competition - Martyniuk, Nicolás Alejandro (2015)
The invasion of natural forest communities by introduced woody species may threat processes that are critical for ecosystem integrity, including plant pollination and reproduction. In particular, invasive conifers (e.g., Pseudotsuga menziesii, Pinus spp.) escaped from forest plantations may impair seed production of anemophilous native conifers by altering the dynamics of wind-borne pollen flow among trees. In this study, we analyzed the effects of invasive conifers on the pollination and sexual reproduction of Andean cedar (Austrocedrus chilensis), a dioecious conifer native to the temperate forests of southern South America. Wind-dispersed pollen captured in pollen traps revealed that the timing of pollen release between the invasive and native conifers overlapped extensively, and the pollen cloud surrounding female cedar trees in invaded forest was heavily contaminated with pollen from the invasive conifers. Increasing abundance of invasive conifers in the proximity of female cedars decreased the local density of air-borne cedar pollen and increased contamination of the pollen cloud with pollen from the invasive conifers. This increased the chance of finding heterospecific pollen from these invaders in the micropyles of the native cedar. In turn, the presence of pollen grains from invasive conifers, particularly of P. menziesii, in the cedar’s micropyles was associated with a strong increase in the percentage of seed abortion. Our results clearly support the hypothesis that invasive conifers can interfere with the pollination and sexual reproduction of native wind-pollinated conifers. Thus, plantations of introduced and highly invasive conifers should not occur in the proximity of stands of native conifers in order to guarantee their reproduction and long-term population viability.